The Role of EREG, PTPN1, and SERPINB7 Genes in the Pathogenesis of Psoriasis: May SERPINB7 Be Protective and a Marker of Severity for Psoriasis? - Ayvaz, Havva Hilal; Öztürk, Kuyaş Hekimler; Seyirci, Mehmet Ali; Atay, Emrah; Korkmaz, Selma; Erturan, İjlal; Yıldırım, Mehmet (Dermatology Practical & Conceptual, 2023)
Introduction: Psoriasis is a chronic inflammatory dermatological disease with complex pathogenesis in which many immune system cells, including keratinocytes, play a role. Many genes regulate the proliferation of keratinocytes and other immune cells that have essential roles in the pathogenesis of psoriasis.The expressions of EREG, PTPN1, and SERPINB7 genes were shown as upregulated in psoriatic skins in a few studies previously.Objectives: We aimed to evaluate the expressions of these genes in psoriatic lesional skin and com-pared them with non-lesional adjacent skin of the same patients and normal skin of healthy controls.Results: Our results revealed that the expressions of EREG and PTPN1 genes were upregulated,whereas the SERPINB7 gene expression was down regulated in the psoriatic skin of the patients than normal skin of controls. Moreover, the expression level of the SERPINB7 gene was also negatively correlated with the severity of the disease among patients.Conclusions: According to our results, overexpression of EREG and PTPN1 genes, and decreased expression of SERPINB7 gene may lead to the development of psoriasis.